Industry-based, transdisciplinary, complex problems as realistic settings for applying the M in STEM. Issue 5 (28th May 2021) - Czaplinski, Iwona; Turner, Ian W.; Helmstedt, Kate; Corry, Paul; Mallet, Dann G.
Abstract : In this paper, we consider the perceived effectiveness of using industry-based transdisciplinary, complex problems as a vehicle for final year undergraduate mathematics students to apply their knowledge and skills in realistic settings, preparing them for the world of work. The discussion centres on a recently designed, implemented and evaluated model for a capstone subject incorporating a work integrated learning project in a Bachelor of Mathematics degree. To provide background for the discussion, we present the motivation for introducing such learning activities into the programme as well as the design of the model itself. We also report on the outcomes of implementation of the Work Integrated Learning experiences, discussing participant perspectives and describing lessons learnt over the two years. We conclude with a set of identified characteristics of capstone experiences in mathematics, and with a call to re-conceptualize the ways design teams collaborate to support academics.